Strategy for Developing Religious Ecotourism in Coastal Areas and Mangrove Forests - Ismail, R. Moh.; Abidin, Muhammad Zaihafiz Zainal; Soeprijadi, Liliek; Perdana, Randiki Gusti; Sulastri, Sri (Politeknik Kelautan dan Perikanan Karawang, 2024)
Coastal areas with mangrove forests are a natural landscape that has a unique environmental tone. In the past, this coastal area was a landing place for traders and religious leaders to preach. Developing this area into religious ecotourism is an economic potential that should be grown from integrated marine space management with sustainable exploration of coastal resources. The research aims to develop implementation strategy stages for the development of religious ecotourism in coastal areas and mangrove forests in the Southeast Asia region. Descriptive research with a qualitative approach. Data was obtained from cross-information between researchers at four different locations. Each researcher obtained empirical data from interviews and direct observations in the field. The implementation strategy was prepared using SWOT-BSC analysis with a combination of weightings, where each researcher reported the two most important aspects in the implementation feasibility approach based on observations at each of their nearest residential locations. Collaborative research provides general results that contain a compilation of different strategies. Aspects of the religious approach and aspects of revitalizing the role of coastal communities and indigenous communities are the main things that must be prioritized from the start to realize religious ecotourism so that it becomes a leading tourist destination in an area.